QUALITY OF LIFE IMPAIRMENTS IN HUNTINGTON'S DISEASE (LITERATURE REVIEW AND OWN DATA) - Usmanov Firdavs Bakhtiyorovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Huntington's disease (HD) is a rare, incurable, hereditary neurological disorder that causes the progressive breakdown of nerve cells in the brain. Huntington's chorea is a progressive neurodegenerative hereditary disorder that is transmitted from generation to generation in an autosomal dominant manner. Huntington's chorea occurs in 4-6 cases per 100,000 population (4-6:100,000). The classic symptom is chorea, which is the appearance of hyperkinesis, i.e. uncontrolled movements. This is one of the  main  features  of  the  disease,  which  is  considered  to  be  the  anticipation phenomenon, i.e. the disease progresses gradually and begins at a young age [1]. The mutant huntingtin gene has a repeat of the trinucleotide sequence CAG from 40 to 80. The  pathogenesis  of  HD  is  multifaceted  and  involves  glutamine  aggregation, mitochondrial and oxidative stress, mitochondrial-related pathway dysfunction, and DNA damage. Currently, two drugs, tetrabenazine and deutetrabenazine, are approved for the treatment of HD.